(untitled) (Iranian Journal of Kidney Diseases, 2011)
Aldosterone, a mineralocorticoid hormone, has a well-known function on water balance and blood pressure homeostasis. Recently, its role in metabolic syndrome, insulin resistance, and obesity has come into a spotlight. Aldosterone induces inflammation and oxidative stress that are attenuated by mineralocorticoid receptor blockers such as spironolactone. Aldosterone exerts its effects via the epithelial sodium channel by non-genomic pathways, including serum and glucocorticoid kinase 1, neural precursor cell-expressed developmentally downregulated (gene 4) protein, and K-Ras, and genomic pathways via epigenetic mechanisms. Beyond regulating epithelial sodium channel, aldosterone induces cardiac hypertrophy, endothelial dysfunction, podocyte injury, and fibrosis. This opens new horizons for mineralocorticoid receptor antagonists and novel therapeutic targets such as serum-glucocorticoid regulated kinase 1.